Skin dryness in apparently healthy human skin is associated with decreased expression of bleomycin hydrolase in the stratum corneum. (11th December 2014) - Son, E. D.; Kim, Y.; Joo, K. M.; Kim, H. J.; Lee, E.; Nam, G. W.; Cho, E. G.; Noh, M.; Chung, J. H.; Byun, S. Y.; Lee, T. R.
Summary Background Maintenance of water balance in the stratum corneum (SC) is determined by the content of intercellular lipids and natural moisturizing factors (NMFs) in corneocytes. Aim To investigate the association between the NMFs and (pro)filaggrin and the proteases responsible for the processing of (pro)filaggrin to NMFs in the SC of hydrated and dry skin areas of healthy human subjects. Methods The SC hydration state and the transepidermal water loss (TEWL) were measured using a Corneometer and a Tewameter, respectively. Proteases, (pro)filaggrin and NMFs were extracted from SC samples obtained by tape‐stripping of the tested skin. Expression levels of (pro)filaggrin were determined by dot blotting and western blotting, and total NMFs by ultra‐high performance liquid chromatography. Expression of the proteases caspase‐14, calpain‐1 and bleomycin hydrolase was measured by western blotting. Results The levels of (pro)filaggrin were not significantly different between hydrated and dry skin, whereas the level of total NMFs was significantly reduced in dry skin. A negative correlation between (pro)filaggrin and NMFs was found in dry skin (Pearson correlation coefficient r = − 0.57, *P < 0.05). Bleomycin hydrolase expression was significantly decreased in the SC of dry skin. Conclusions These results suggest that the low hydration state of dry skin may be due to the reduction in (pro)filaggrin degradation caused by decreased bleomycin hydrolase expression.